Anthropogenic contaminants in freshwater from the northern Antarctic Peninsula region - Domínguez-Morueco, Noelia; Moreno Merino, Luis; Molins-Delgado, Daniel; Díaz-Cruz, M. Silvia; Aznar-Alemany, Òscar; Eljarrat, Ethel; Farré, Marinella; López Martínez, Jerónimo; López de Alda, Miren; Silva, Adrián; Durán Valsero, Juan José; Valcárcel, Yolanda (Ambio, 2020)
This study aimed to evaluate the presence of ultraviolet filters (UV-Fs), benzotriazoles, pyrethroids and per- and polyfluoroalkyl substances (PFASs) in freshwater and wastewater from the northern Antarctic Peninsula region. All water samples analyzed contained UV-Fs residues and high concentrations were detected in anthropogenic impacted sites (< LOD up to 1300 ng/L). Likewise, benzotriazoles were detected in all water samples (< LOQ–920 ng/L). Regarding suspended particulate matter, almost all UV-Fs and all benzotriazoles were measured at concentrations ranging from < LOQ to 33 µg/g dry weight. Pyrethroids were also detected (< LOQ–250 ng/L) and their presence implies the existence of a gateway to the Antarctica Peninsula from other regions. The data confirmed the presence of PFASs (< LOD–7500 ng/L) in this area, in agreement with previous studies. In light of these results, extended monitoring in Antarctica should be carried out to perform a reliable environmental risk assessment leading to propose recommendations to minimize the anthropic impact. This research was supported by projects CTM2011-26372, CTM2013-57119, and CTM2014-57119-R of the Spanish National R+D Plan, and PICTO 2005N36155 of the Secretariat for Science and Technology and the Argentine Antarctic Institute. This study also received funding from the Generalitat de Catalunya (Consolidated Research Group “2017 SGR 01404—Water and Soil Quality Unit”) and from the European Union’s Seventh Framework Program for research, technological development, and demonstration under Grant Agreement No. 603437. This research is part of POLARCSIC activities. It reflects only the authors’ views. The Community is not liable for any use that may be made of the information contained therein. The authors would like to thank the logistical support provided by the Spanish, Argentinean, and Chilean Antarctic programs for conducting the fieldwork. The reviewers and editor are also acknowledged for their contribution to improve the article. Peer reviewed